The Scissors Model of Microcrack Detection in Bone: Work in Progress - TAYLOR, DAVID; MULCAHY, LAUREN; TISBO, PIETRO; DOOLEY, CLODAGH; DUFFY, GARRY (My University, 2010)
We have proposed a new model for microcrack detection by osteocytes in bone. According to this model, cell signalling is initiated by the cutting of cellular processes which span the crack. We show that shear displacements of the crack faces are needed to rupture these processes, in an action similar to that of a pair of scissors. Current work involves a combination of cell biology experiments, theoretical and experimental fracture mechanics and system modelling using control theory approaches. The approach will be useful for understanding effects of extreme loading, aging, disease states and drug treatments on bone damage and repair; the present paper presents recent results from experiments and simulations as part of current, ongoing research.
PUBLISHED
Keywords: Bioengineering; Bone fracture; Next Generation Medical Devices